PENGARUH MODEL DISCOVERY LEARNING TERHADAP KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS X SMK NEGERI 8 PADANG - Anggina, Wida; Thamsin, Andria Catri (Universitas Negeri Padang, 2019)
ABSTRACTÂ This study aims to describe the influence model of discovery learning the skills of writing text exposition class X SMKN 8 Padang. The type of this research is quantitative research done using experimental design. The results of this research are three: (1) writing text skills exposition before using discovery learning model of class X SMKN 8 Padang are in qualifying Nearly Enough (HC) with an average value of 50,12 (2) writing text skills exposition after using discovery learning model of class X SMKN 8 Padang are in qualification well (B) with an average value of 80,98 and (3) exposition writing text skills class X SMKN 8 Padang after using the model of discovery learning better than before using the model of discovery learning.Â Kata Kunci: Pengaruh, Model Discovery Learning, Teks Eksposisi